Size‐Dependent Toxicity of Gold Nanoparticles on Human Embryonic Stem Cells and Their Neural Derivatives. Issue 5 (16th December 2015) - Senut, Marie‐Claude; Zhang, Yanhua; Liu, Fangchao; Sen, Arko; Ruden, Douglas M.; Mao, Guangzhao
Abstract : This study explores the use of human embryonic stem cells (hESCs) for assessing nanotoxicology, specifically, the effect of gold nanoparticles (AuNPs) of different core sizes (1.5, 4, and 14 nm) on the viability, pluripotency, neuronal differentiation, and DNA methylation of hESCs. The hESCs exposed to 1.5 nm thiolate‐capped AuNPs exhibit loss of cohesiveness and detachment suggesting ongoing cell death at concentrations as low as 0.1 μg mL −1 . The cells exposed to 1.5 nm AuNPs at this concentration do not form embryoid bodies but rather disintegrate into single cells within 48 h. Cell death caused by 1.5 nm AuNPs also occur in hESC‐derived neural progenitor cells. None of the other nanoparticles exhibit toxic effects on the hESCs at concentrations as high as 10 μg mL −1 during a 19 d neural differentiation period. Thiolate‐capped 4 nm AuNPs at 10 μg mL −1 cause a dramatic decrease in global DNA methylation (5 mC) and a corresponding increase in global DNA hydroxymethylation (5 hmC) of the hESC's DNA in only 24 h. This work identifies a type of AuNPs highly toxic to hESCs and demonstrates the potential of hESCs in predicting nanotoxicity and characterizing their ability to alter the DNA methylation and hydroxymethylation patterns in the cells. Abstract : The differentiation of human embryonic stem cells (hESCs) into neurons is used to assess the morphological and epigenetic effects of exposure to gold nanoparticles (AuNPs). Ultrasmall AuNPs are highly toxic to hESCs and their neural derivatives. This work demonstrates the potentials of stem cells in predicting nanotoxicity and will help to define the health risks of nanoparticles.